Cybervictimization and cyberbullying among college students: The chain mediating effects of stress and rumination - Luo, Qing; Wu, Na; Huang, Lu (Frontiers in Psychology, 2023)
The popularity of the Internet has led to an increase in cybervictimization and cyberbullying. Many studies have focused on the factors influencing cybervictimization or cyberbullying, but few have researched the mechanism that mediates these phenomena. Therefore, in this study, we use a chain mediation model to explore the mechanisms of cybervictimization and cyberbullying. This research is based on the general aggression model and examines whether stress and rumination play a mediating role in the relationship between cybervictimization and cyberbullying among Chinese college students. This study included 1,299 Chinese college students (597 men and 702 women, M = 21.24 years, SD = 3.16) who completed questionnaires on cybervictimization, stress, rumination, and cyberbullying. Harman’s one-factor test was used to analyze common method bias; mean and standard deviations were used to analyze the descriptive statistics, Pearson’s moment correlation was used to determine the relationship between variables, and Model 6 of the SPSS macro examined the mediating effect of stress and rumination. The results indicate that rumination mediated the relationship between cybervictimization and cyberbullying. In addition, stress and rumination acted as a chain mediator in this association. These results have the potential to reduce the likelihood of college students engaging in cyberbullying as a result of cybervictimization, minimize the rate of cyberbullying among youths, and lead to the development of interventions for cybervictimization and cyberbullying.